1988
DOI: 10.1007/bf03010620
|View full text |Cite
|
Sign up to set email alerts
|

Prospective assessment of a protocol for selective ordering of preoperative chest x-rays

Abstract: Routine preoperative chest x-rays are still widely employed worldwide, although results of many studies do not support their broad utilization. A protocol for selective ordering of preoperative chest x-rays, according to the patient's clinical status, medical history and scheduled surgery, was developed and implemented in a teaching hospital in Paris. The utilization of the protocol during a one-year period was evaluated. Eleven hundred and one chest x-rays were ordered in 3866 patients (28 per cent). Five hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
1
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 7 publications
1
13
1
1
Order By: Relevance
“…54 One scenario in which preoperative chest X-rays may be of value is in ruling out metastases in the patients with a known malignancy. 55 Currently, a preoperative chest X-ray is recommended only for patients with acute pulmonary abnormalities, questionable metastatic disease, patients with CHF, elderly patients, a long-standing history of smoking, and recent migrants from endemic countries. 56…”
Section: Chest Radiographmentioning
confidence: 99%
“…54 One scenario in which preoperative chest X-rays may be of value is in ruling out metastases in the patients with a known malignancy. 55 Currently, a preoperative chest X-ray is recommended only for patients with acute pulmonary abnormalities, questionable metastatic disease, patients with CHF, elderly patients, a long-standing history of smoking, and recent migrants from endemic countries. 56…”
Section: Chest Radiographmentioning
confidence: 99%
“…Several reports have also considered whether the information obtained from routine preoperative radiographs have had or might have had, any influence on health outcomes. 15,[17][18][19]29 Since this test, when carded out on large numbers of patients, is associated with considerable costs and some health effects, it is important to establish the frequency with which new information of.clinical value is obtained, The present report describes a meta-analysis of published studies and was carried out with the object of estimating this frequency with greater confidence than could be derived from any individual report on its own. Unfortunate.ly, there is insufficient evidence on which to base estimates of how frequently information resulting from routine radiography influences health outcomes.…”
Section: Sont Indus Clans La M~ta-analyse En Moyenne Des Anomalies mentioning
confidence: 99%
“…Charpak et al 16 , in an analysis of surgical patients who underwent a chest X-ray with a clinical indication identified that 52% had abnormalities in the examination, but in only 23% of the cases, these abnormalities were not expected by anamnesis and physical examination. Also in this study, the observed changes modified the anesthetic-surgical management in only 5% of the cases.…”
mentioning
confidence: 99%